Pediatric Sepsis Research: Where Are We and Where Are We Going? - Massaud-Ribeiro, Letícia; Silami, Pedro Henrique Nunes Costa; Lima-Setta, Fernanda; Prata-Barbosa, Arnaldo (Frontiers in Pediatrics, 2022)
Sepsis continues to be one of the leading causes of admission to the Pediatric Intensive Care Unit, representing a great challenge for researchers and healthcare staff. This mini review aims to assess research on pediatric sepsis over the years. Of the 2,698 articles retrieved from the Scopus database, the 100 most cited were selected (50 published since 2000 and 50 published since 2016). The most cited studies, published in the 21st century, are highlighted, with their main findings and perspectives.